Plasma miR-323 as a Biomarker for Screening Papillary Thyroid Cancer From Healthy Controls - Liu, Yang; Li, Lin; Liu, Zheng; Yuan, Qingling; Lu, Xiubo (Frontiers in Medicine, 2020)
The present study aims to evaluate whether plasma miR-323 serves as a potential biomarker to screen patients with papillary thyroid cancer (PTC) from healthy controls. Real-time PCR was performed to evaluate miR-323 expression in healthy controls, benign thyroid nodule (BTN) and PTC patients. Receiver operating characteristic (ROC) curve analysis was used to evaluate whether plasma miR-323 could be used to screen PTC patients from BTN patients and healthy controls. Plasma miR-323 was significantly increased in PTC patients compared with that in BNT patients and healthy controls. Moreover, miR-323 in the thyroid tissue was significantly increased in PTC patients when compared to BNT patients. We further showed that plasma and tissue miR-323 levels were significantly increased in PTC patients with metastasis compared to those without metastasis. Plasma miR-323 was significantly increased in PTC patients with BRAF V600E mutation when compared to those with wild-type BRAF. Furthermore, plasma miR-323 was significantly increased in PTC patients with higher Tg-FNAB. ROC analysis showed that plasma miR-323 could distinguish PTC patients from BNT patients and healthy controls. The present study demonstrated that plasma miR-323 might be an effective noninvasive indicator for PTC progression and serve as a biomarker for the diagnosis of PTC.